Implementation of a Solar-Wind Hybrid System for the Posong Nature Tourism Food Court in Tlahab Village, Temanggung Regency - Asnawi, Rustam; Nurhening Yuniarti; Slamet Widodo; Dwi Otik Kurniawati; Pinandita, Satria (Journal of Community Empowerment, 2025)
This community service activity was carried out by a team of lecturers and students of Yogyakarta State University (UNY) in Tlahap Village, Kledung District, Temanggung Regency, specifically in the Posong Nature Tourism area. The background of this activity was the limited access to electricity faced by the community managing food courts in the tourist area due to the lack of optimal PLN network coverage. This has an impact on low service quality, limited stall operating hours, and lack of comfort for tourists. Therefore, the community service team presented a renewable energy-based solution in the form of a hybrid system of Solar Power Plants (PLTS) and wind turbines with a capacity of 1,500 watts and 5,000 Wh of energy storage. The method of implementing the activity was carried out through an energy needs survey, socialization, device installation, technical training, and monitoring and evaluation. The community service activity was carried out on August 8, 2025, at 10:00 WIB until finished, attended by the Head of Tlahap Village, the Chairperson and management of Posong Nature Tourism, and 23 local residents, with cloudy and foggy weather conditions but proceeded smoothly. Participants were given an understanding of renewable energy systems, maintenance techniques, handling electrical short circuits, and power usage management to prevent batteries from draining quickly. The results of discussions with the community showed that the application of renewable energy not only provides a solution to electricity needs, but also increases the community's capacity to manage electrical engineering systems independently. Furthermore, the availability of electricity supports the development of food court businesses, tourist comfort, and strengthens Posong's image as an eco-tourism destination. This activity contributes to the achievement of the Sustainable Development Goals (SDG 7: Affordable and Clean Energy, SDG 8: Decent Work and Economic Growth, and SDG 13: Addressing Climate Change).